Untouchable Bodies, Resistance, and Liberation : A Comparative Theology of Divine Possessions - Samuel, Joshua, (Currents of Encounter ;, 2020)
In Untouchable Bodies, Resistance, and Liberation, Joshua Samuel constructs an embodied comparative theology of liberation by comparing divine possessions among Hindu and Christian Dalits in South India. Critiquing the problems inherent in prioritizing texts when studying religious traditions, Samuel calls for the need to engage in body and people centered interreligious learning. This comparative theological reading of ecstatic experiences of the divine in Dalit bodies in Hinduism and Christianity brings out the powerful liberative potential inherent in the bodies of the oppressed, enabling us to identify alternative modes of resistance and new avenues of liberation among those who are dehumanized and discriminated, and to find deeper and meaningful ways of speaking about God in the context of oppression.